Fibroin-based composite aerogel material for adsorbing heavy metals as well as preparation method and application of fibroin-based composite aerogel material
By blending the silk fibroprotein solution prepared from waste silk with nano-scale adsorbent, silk fibro-based composite aerogel material is prepared, which solves the problems of adsorbent agglomeration and uneven distribution of ferrous chloride, and achieves efficient heavy metals Adsorption, especially in textile printing and dyeing wastewater removal.
Patent Information
- Application Number
- CN202411499511.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-13
AI Technical Summary
Existing adsorbents are prone to agglomeration at the nanoscale, which affects the adsorption efficiency, and ferrous chloride is distributed unevenly in the aerogel, affecting the adsorption effect of heavy metals.
The silk fibroprotein solution is used to prepare the silk fibroprotein solution and blend it with the nano-scale adsorbent, and the silk fibroprotein composite aerogel material is prepared through high-speed dispersion and freeze-drying to ensure uniform dispersion of the nano-scale adsorbent, providing multiple binding sites, and avoiding agglomeration.
The prepared silk fibro-based composite aerogel material has a high specific surface area and good stability, which significantly improves the adsorption rate and adsorption capacity of heavy metals, especially with high efficiency removal ability for metal antimony.
Smart Images

Figure CN119114022A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of high-performance adsorption materials, and more specifically, to a silk-based composite aerogel material for adsorbing heavy metals, and a preparation method and application thereof. Background Art
[0002] Printing and dyeing is a key link in the textile industry. The colorful, multifunctional and high value-added textile products are mostly completed through dyeing and finishing. In recent years, environmental protection laws and regulations such as the "Environmental Protection Law of the People's Republic of China" and the "Water Pollutant Emission Standards for Textile Dyeing and Finishing Industry" have been introduced one after another. The printing and dyeing industry is facing tremendous pressure and challenges in ecological and environmental protection. How to improve the deep treatment effect of wastewater and reduce the pollution of printing and dyeing wastewater to the environment has become a research hotspot, which is also the key to the sustainable development of the printing and dyeing industry.
[0003] At present, the main methods for removing heavy metals from textile dyeing and finishing wastewater include coagulation and sedimentation, adsorption and electrochemical methods, etc. Among them, adsorption is a simple and easy water treatment technology with the advantages of low cost, high efficiency and easy operation. However, when the particle size of the adsorbent reaches the nanoscale, it is very easy to agglomerate, thus affecting the adsorption efficiency of the adsorbent.
[0004] In order to solve the above problems, a Chinese patent with publication number CN108325506A published on July 27, 2018 provides a method for preparing a modified cellulose aerogel for adsorbing heavy metals; the method uses corn stalks as raw materials to prepare cellulose aerogels, and prepares the modified cellulose aerogels by adding methacrylate, maleic acid, and a mixed solution of hydrogen peroxide and ferrous chloride to the cellulose aerogels. The modified cellulose aerogel is prepared by adding ferrous chloride to the cellulose aerogels. This method may cause the ferrous chloride to be unevenly distributed in the aerogels, thereby affecting the adsorption of heavy metals by the adsorbent.
[0005] Therefore, there is an urgent need to provide an aerogel with high adsorption, good stability and not prone to agglomeration, and a method for preparing the aerogel. Summary of the invention
[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing a silk-based composite aerogel material for adsorbing heavy metals; the method uses waste silk as a raw material to prepare a silk fibroin solution, which is then mixed with a nanoscale adsorbent to prepare a silk-based composite aerogel material; a second purpose is to provide a silk-based composite aerogel material prepared by the method and the application of the silk-based composite aerogel material for adsorbing heavy metals in textile printing and dyeing wastewater.
[0007] To solve the above problems, the present invention adopts the following technical solutions.
[0008] A method for preparing a silk-based composite aerogel material for adsorbing heavy metals, the specific preparation method is as follows:
[0009] (1) Using silk as raw material, degumming to obtain degummed silk, and then fully mixing it with a ternary system mixed solution, centrifuging, and dialyzing to obtain a silk fibroin solution;
[0010] (2) mixing the nanoscale adsorbent and the silk fibroin solution at a certain mass fraction;
[0011] (3) High-speed dispersion and freeze-drying of the solution blended in step (2) are performed to prepare a silk-based composite aerogel material.
[0012] Furthermore, in step (1), the silk is waste silk textiles, waste cocoon silk, inferior cocoons, silk cocoon waste, waste spun silk, and waste silk in the silk making or silk weaving process; the waste silk textiles are any one or more mixtures of silk scarves, silk clothing, silk quilts and silk decorations.
[0013] Furthermore, in the degumming operation in step (1), a degumming agent is used, and the degumming agent is a 0.5wt% sodium carbonate solution, and the bath ratio of silk to sodium carbonate solution is 1:80-100.
[0014] Furthermore, the ternary system mixed solution in step (1) is a mixture of CaCl2, C2H5OH and H2O; the molar ratio of CaCl2, C2H5OH and H2O is 1:2:8.
[0015] Furthermore, in the step (1), the mass ratio of the degummed silk to the ternary system mixed solution is 1:6-9; the reaction temperature is 50-70°C; and the reaction time is 50-150 min.
[0016] Furthermore, in step (1), the mass ratio of the degummed silk to the ternary system mixed solution is preferably 1:9; the reaction temperature is preferably 60° C.; and the reaction time is preferably 60 min.
[0017] Furthermore, in the step (1), the centrifuge speed is 5000-7500 rpm, and the centrifugation time is 6-10 min.
[0018] Furthermore, in the step (2), the mixing mass ratio of the silk fibroin solution to the nanoscale adsorbent is 1:1-10.
[0019] Furthermore, in the step (2), the nanoscale adsorbent is nanoscale ferric oxide, nanoscale ferrosoferric oxide or nanoscale aluminum oxide, and the particle size of the nanoscale adsorbent is less than 100 nm.
[0020] Furthermore, in the step (3), the speed of high-speed dispersion is 500-2000 r / min, and the dispersion time is 10-40 min.
[0021] Furthermore, the specific operation of freeze drying in step (3) is freezing at -70 to -40°C for 4 to 10 hours and then vacuum drying.
[0022] Furthermore, the specific operation of freeze drying in step (3) is vacuum drying after liquid nitrogen treatment.
[0023] The present invention also provides a method for preparing the silk fibroin-based composite aerogel material by using the silk fibroin-based composite aerogel material capable of absorbing heavy metals.
[0024] The present invention also provides an application of a silk-based composite aerogel material in adsorbing heavy metals, including using the silk-based composite aerogel material for adsorbing heavy metals in textile printing and dyeing wastewater.
[0025] Compared with the prior art, the advantages of the present invention are:
[0026] 1. The preparation method of the silk-based composite aerogel material provided in this scheme uses waste silk as the source of the silk protein solution, which effectively improves the recycling of waste silk, reduces the impact of waste silk on the environment, and significantly reduces the production cost of the silk-based composite aerogel material. The silk protein solution is mixed with a nano-scale adsorbent and then freeze-dried to prepare a silk-based composite aerogel material; this preparation method enables the nano-scale adsorbent to be evenly dispersed in the silk aerogel, and provides multiple binding sites for the nano-scale adsorbent to prevent it from agglomerating, and at the same time enables the prepared silk-based composite aerogel material to exhibit stable heavy metal adsorption performance.
[0027] 2. The silk-based composite aerogel material prepared in this scheme has a high BET specific surface area and provides more adsorption sites, so that the silk-based composite aerogel material can effectively adsorb heavy metal pollutants in water bodies; in addition, the silk-based composite aerogel material has a high adsorption rate and adsorption capacity for heavy metal antimony, and can effectively remove metallic antimony from water bodies contaminated by heavy metals. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope image of the silk fibroin-based composite aerogel material of Example 1;
[0029] Figure 2 This is a graph showing the variation of the adsorption efficiency of the silk-based composite aerogel material of Example 1 over time;
[0030] Figure 3 This is a graph showing the change in adsorption capacity of the silk-based composite aerogel material of Example 1 over time;
[0031] Figure 4 This is a diagram showing the removal efficiency of heavy metals in wastewater by the silk-based composite aerogel material of Example 1. DETAILED DESCRIPTION
[0032] Embodiment 1:
[0033] (1) Preparation of degummed silk
[0034] A 0.5wt% sodium carbonate solution is prepared, and corresponding masses of silk and sodium carbonate solution are weighed according to a bath ratio of 1:100. After the temperature in the water bath rises to 100°C, the two are mixed, heated at a constant temperature for 30 minutes, and then taken out. After being taken out, the degummed silk is washed with deionized water for multiple times, and the above steps are repeated three times; the washed degummed silk is dried in a 50°C blast oven to obtain dry degummed silk.
[0035] (2) Preparation of silk fibroin solution
[0036] A CaCl2 / C2H5OH / H2O ternary system mixed solution with a molar ratio of 1:2:8 was prepared; the degummed silk and the ternary system mixed solution were fully mixed at a bath ratio of 1:9, and heated in a constant temperature water bath at 60°C for 60 minutes to obtain a light yellow silk fibroin solution; the silk fibroin solution obtained above was placed in a dialysis bag, and dialyzed under a flowing water device for 2 hours; then it was dialyzed in deionized water, the deionized water was replaced every 12 hours, and it was taken out after 96 hours; finally, the dialyzed silk fibroin solution was centrifuged to remove impurities, the centrifugal speed was 5000-7500rpm, the centrifugal time was 8 minutes, the operation was repeated 5 times, the silk fibroin solution was obtained, and it was stored at low temperature for use.
[0037] (3) Preparation of Nano-sized Iron Oxide
[0038] Take an appropriate amount of polyethylene glycol (PEG2400) and add it to agate; weigh FeCl3 and NaOH with a molar ratio of 1:3, place them in the agate containing PEG2400 at room temperature and grind them thoroughly for 30 minutes; the solid phase product is washed alternately with double distilled water and alcohol for three times, filtered and dried naturally to obtain a crude product; then the crude product is placed in a muffle furnace and calcined at 400℃ for 2h, and nano-sized ferric oxide particles are obtained after grinding and sieving.
[0039] (4) Preparation of silk fibroin / nanoscale iron oxide composite aerogel
[0040] Nano-scale ferric oxide and silk fibroin solution were weighed in a mass ratio of 1:1, and mixed evenly in a high-speed disperser to obtain a silk fibroin mixed solution. The speed of the disperser was 800 r / min, and the time was 20 min. The silk fibroin mixed solution was evenly divided into several disposable culture dishes, pre-frozen for 8 h or treated with liquid nitrogen, and then wrapped with plastic wrap and pierced with holes, and freeze-dried to obtain silk fibroin / nano-scale ferric oxide composite aerogel; the aerogel was sealed in a plastic bag and stored in an electronic moisture-proof box.
[0041] The scanning electron microscope image of the silk fibroin / nanoscale ferric oxide composite aerogel prepared in this example is shown in FIG. Figure 1 ;from Figure 1 It can be seen that the composite aerogel prepared by this method has an irregular appearance. It can be clearly found that there are many irregular and dense pores on the surface of the silk fibroin / nano-scale ferric oxide composite aerogel. These pores give the silk fibroin / nano-scale ferric oxide composite aerogel a loose network structure.
[0042] Embodiment 2:
[0043] (1) Preparation of degummed silk
[0044] A 0.5wt% sodium carbonate solution is prepared, and corresponding masses of silk and sodium carbonate solution are weighed according to a bath ratio of 1:100. After the temperature in the water bath rises to 100°C, the two are mixed, heated at a constant temperature for 30 minutes, and then taken out. After being taken out, the degummed silk is washed with deionized water for multiple times, and the above steps are repeated three times; the washed degummed silk is dried in a 50°C blast oven to obtain dry degummed silk.
[0045] (2) Preparation of silk fibroin solution
[0046] A CaCl2 / C2H5OH / H2O ternary system mixed solution with a molar ratio of 1:2:8 was prepared; the degummed silk and the ternary system mixed solution were fully mixed at a bath ratio of 1:9, and heated in a constant temperature water bath at 60°C for 60 minutes to obtain a light yellow silk fibroin solution; the silk fibroin solution obtained above was placed in a dialysis bag, and dialyzed under a flowing water device for 2 hours; then it was dialyzed in deionized water, the deionized water was replaced every 12 hours, and it was taken out after 96 hours; finally, the dialyzed silk fibroin solution was centrifuged to remove impurities, the centrifugal speed was 5000-7500rpm, the centrifugal time was 8 minutes, the operation was repeated 5 times, the silk fibroin solution was obtained, and it was stored at low temperature for use.
[0047] (3) Preparation of Nano-aluminum Oxide
[0048] 30wt% aluminum nitrate was added to 70wt% nitric acid solution with a concentration of 2.0mol / L, and stirred until completely dissolved to obtain 75mL aluminum dispersion solution. The aluminum dispersion solution was then transferred to a three-necked flask and placed in a reflux device of a glycerol bath and heated to 98°C, and a sodium hydroxide solution with a concentration of 0.80mol / L was added at a stirring speed of 1200r / min, and refluxed at a stirring speed of 1200r / min for 9h, and then centrifuged at a speed of 50000r / min to obtain a white precipitate after centrifugation for 10min; the obtained white precipitate was washed with 95°C water, a mixed solution of ethanol and water with a volume ratio of 4:6 at 50°C, and anhydrous ethanol at room temperature, and then vacuum dried at 50°C to obtain nano-scale aluminum oxide particles.
[0049] (4) Preparation of silk fibroin / nano-aluminum oxide composite aerogel
[0050] Nano-aluminum oxide particles and silk fibroin solution were weighed in a mass ratio of 1:1, and mixed evenly by a high-speed disperser to obtain a silk fibroin mixed solution. The speed of the disperser was 800 r / min, and the dispersion time was 20 min. The silk fibroin mixed solution was evenly divided into several disposable culture dishes, pre-frozen for 8 h (or treated with liquid nitrogen), and then wrapped with plastic wrap and pierced with holes, and freeze-dried to obtain silk fibroin / nano-aluminum oxide composite aerogels; the aerogels were sealed in plastic bags and stored in electronic moisture-proof boxes.
[0051] Embodiment 3:
[0052] (1) Preparation of degummed silk
[0053] Prepare 0.5wt% sodium carbonate solution, weigh corresponding masses of silk and sodium carbonate solution according to a bath ratio of 1:100, wait until the temperature in the water bath rises to 100°C, mix the two and heat at a constant temperature for 30 minutes, then take out, wash with deionized water for multiple times, and repeat the above steps three times; dry the washed degummed silk in a 50°C blast oven to obtain dry degummed silk.
[0054] (2) Preparation of silk fibroin solution
[0055] A CaCl2 / C2H5OH / H2O ternary system mixed solution with a molar ratio of 1:2:8 was prepared; the degummed silk and the ternary system mixed solution were fully mixed at a bath ratio of 1:9, and heated in a constant temperature water bath at 60°C for 60 minutes to obtain a light yellow silk fibroin solution; the silk fibroin solution obtained above was placed in a dialysis bag, and dialyzed under a flowing water device for 2 hours; then it was dialyzed in deionized water, the deionized water was replaced every 12 hours, and it was taken out after 96 hours; finally, the dialyzed silk fibroin solution was centrifuged to remove impurities, the centrifugal speed was 5000-7500rpm, the centrifugal time was 8 minutes, the operation was repeated 5 times, the silk fibroin solution was obtained, and it was stored at low temperature for use.
[0056] (3) Preparation of Nano-sized Iron Oxide
[0057] Take an appropriate amount of polyethylene glycol (PEG2400) and add it to agate; weigh FeCl3 and NaOH with a molar ratio of 1:3, place them in the agate containing PEG2400 at room temperature and grind them thoroughly for 30 minutes; the solid phase product is washed alternately with double distilled water and alcohol for three times, filtered and dried naturally to obtain a crude product; then the crude product is placed in a muffle furnace and calcined at 400°C for 2 hours, and after grinding and sieving, nano-sized ferric oxide particles are obtained.
[0058] (4) Preparation of silk fibroin / nanoscale iron oxide composite aerogel
[0059] The silk fibroin solution and nano-iron trioxide were weighed in a mass ratio of 1:6, and mixed evenly in a high-speed disperser to obtain a silk fibroin mixed solution. The speed of the disperser was 800 r / min, and the time was 20 min. The silk fibroin mixed solution was evenly divided into several disposable culture dishes, pre-frozen for 8 h (or treated with liquid nitrogen), and then wrapped with plastic wrap and pierced with holes, and freeze-dried to obtain silk fibroin / nano-iron trioxide composite aerogel; the aerogel was sealed in a plastic bag and stored in an electronic moisture-proof box.
[0060] Embodiment 4:
[0061] (1) Preparation of degummed silk
[0062] A 0.5wt% sodium carbonate solution is prepared, and corresponding masses of silk and sodium carbonate solution are weighed according to a bath ratio of 1:100. After the temperature in the water bath rises to 100°C, the two are mixed, heated at a constant temperature for 30 minutes, and then taken out. After being taken out, the degummed silk is washed with deionized water for multiple times, and the above steps are repeated three times; the washed degummed silk is dried in a 50°C blast oven to obtain dry degummed silk.
[0063] (2) Preparation of silk fibroin solution
[0064] A CaCl2 / C2H5OH / H2O ternary system mixed solution with a molar ratio of 1:2:8 was prepared; the degummed silk and the ternary system mixed solution were fully mixed at a bath ratio of 1:9, and heated in a constant temperature water bath at 60°C for 60 minutes to obtain a light yellow silk fibroin solution; the silk fibroin solution obtained above was placed in a dialysis bag, and dialyzed under a flowing water device for 2 hours; then it was dialyzed in deionized water, the deionized water was replaced every 12 hours, and it was taken out after 96 hours; finally, the dialyzed silk fibroin solution was centrifuged to remove impurities, the centrifugal speed was 5000-7500rpm, the centrifugal time was 8 minutes, the operation was repeated 5 times, the silk fibroin solution was obtained, and it was stored at low temperature for use.
[0065] (3) Preparation of Nano-sized Iron Oxide
[0066] Take an appropriate amount of polyethylene glycol (PEG2400) and add it to agate; weigh FeCl3 and NaOH with a molar ratio of 1:3, place them in the agate containing PEG2400 at room temperature and grind them thoroughly for 30 minutes; the solid phase product is washed alternately with double distilled water and alcohol for three times, filtered and dried naturally to obtain a crude product; then the crude product is placed in a muffle furnace and calcined at 400°C for 2 hours, and then ground and sieved to obtain nano-sized ferric oxide particles.
[0067] (4) Preparation of silk fibroin / nanoscale iron oxide composite aerogel
[0068] The silk fibroin solution and nano-iron trioxide were weighed in a mass ratio of 1:10, and mixed evenly in a high-speed disperser to obtain a silk fibroin mixed solution. The speed of the disperser was 800 r / min, and the time was 20 min. The silk fibroin mixed solution was evenly divided into several disposable culture dishes, pre-frozen for 8 h (or treated with liquid nitrogen), and then wrapped with plastic wrap and pierced with holes, and freeze-dried to obtain silk fibroin / nano-iron trioxide composite aerogel; the aerogel was sealed in a plastic bag and stored in an electronic moisture-proof box.
[0069] Embodiment 5:
[0070] (1) Preparation of degummed silk
[0071] A 0.5wt% sodium carbonate solution is prepared, and corresponding masses of silk and sodium carbonate solution are weighed according to a bath ratio of 1:100. After the temperature in the water bath rises to 100°C, the two are mixed, heated at a constant temperature for 30 minutes, and then taken out. After being taken out, the degummed silk is washed with deionized water for multiple times, and the above steps are repeated three times; the washed degummed silk is dried in a 50°C blast oven to obtain dry degummed silk.
[0072] (2) Preparation of silk fibroin solution
[0073] A CaCl2 / C2H5OH / H2O ternary system mixed solution with a molar ratio of 1:2:8 was prepared; the degummed silk and the ternary system mixed solution were fully mixed at a bath ratio of 1:6, and heated in a constant temperature water bath at 70°C for 150 minutes to obtain a light yellow silk fibroin solution; the silk fibroin solution obtained above was placed in a dialysis bag, and dialyzed under a flowing water device for 2 hours; then it was dialyzed in deionized water, the deionized water was replaced every 12 hours, and it was taken out after 96 hours; finally, the dialyzed silk fibroin solution was centrifuged to remove impurities, the centrifugal speed was 5000-7500rpm, the centrifugal time was 8 minutes, the operation was repeated 5 times, the silk fibroin solution was obtained, and it was stored at low temperature for use.
[0074] (3) Preparation of Nano-sized Iron Oxide
[0075] Take an appropriate amount of polyethylene glycol (PEG2400) and add it to agate; weigh FeCl3 and NaOH with a molar ratio of 1:3, place them in the agate containing PEG2400 at room temperature and grind them thoroughly for 30 minutes; the solid phase product is washed alternately with double distilled water and alcohol for three times, filtered and dried naturally to obtain a crude product; then the crude product is placed in a muffle furnace and calcined at 400℃ for 2h, and nano-sized ferric oxide particles are obtained after grinding and sieving.
[0076] (4) Preparation of silk fibroin / nanoscale iron oxide composite aerogel
[0077] Nano-ferric oxide and silk fibroin solution were weighed in a mass ratio of 1:1, and mixed evenly in a high-speed disperser to obtain a silk fibroin mixed solution. The disperser speed was 1000 r / min and the time was 30 min. The silk fibroin mixed solution was evenly divided into several disposable culture dishes, treated with liquid nitrogen, and then wrapped with plastic wrap and pierced with holes, and freeze-dried to obtain silk fibroin / nano-ferric oxide composite aerogels; the aerogels were sealed in plastic bags and stored in electronic moisture-proof boxes.
[0078] Embodiment 6:
[0079] (1) Preparation of degummed silk
[0080] A 0.5wt% sodium carbonate solution is prepared, and corresponding masses of silk and sodium carbonate solution are weighed according to a bath ratio of 1:100. After the temperature in the water bath rises to 100°C, the two are mixed, heated at a constant temperature for 30 minutes, and then taken out. After being taken out, the degummed silk is washed with deionized water for multiple times, and the above steps are repeated three times; the washed degummed silk is dried in a 50°C blast oven to obtain dry degummed silk.
[0081] (2) Preparation of silk fibroin solution
[0082] A CaCl2 / C2H5OH / H2O ternary system mixed solution with a molar ratio of 1:2:8 was prepared; the degummed silk and the ternary system mixed solution were fully mixed at a bath ratio of 1:10, and heated in a constant temperature water bath at 60°C for 30 minutes to obtain a light yellow silk fibroin solution; the silk fibroin solution obtained above was placed in a dialysis bag, and dialyzed under a flowing water device for 2 hours; then it was dialyzed in deionized water, the deionized water was replaced every 12 hours, and it was taken out after 96 hours; finally, the dialyzed silk fibroin solution was centrifuged to remove impurities, the centrifugal speed was 5000-7500rpm, the centrifugal time was 8 minutes, the operation was repeated 5 times, the silk fibroin solution was obtained, and it was stored at low temperature for use.
[0083] (3) Preparation of Nano-sized Iron Oxide
[0084] Take an appropriate amount of polyethylene glycol (PEG2400) and add it to agate; weigh FeCl3 and NaOH with a molar ratio of 1:3, place them in the agate containing PEG2400 at room temperature and grind them thoroughly for 30 minutes; the solid phase product is washed alternately with double distilled water and alcohol for three times, filtered and dried naturally to obtain a crude product; then the crude product is placed in a muffle furnace and calcined at 400°C for 2 hours, and after grinding and sieving, nano-sized ferric oxide particles are obtained.
[0085] (4) Preparation of silk fibroin / nanoscale iron oxide composite aerogel
[0086] Nano-scale ferric oxide and silk fibroin solution were weighed in a mass ratio of 1:1, and mixed evenly in a high-speed disperser to obtain a silk fibroin mixed solution. The speed of the disperser was 1500 r / min, and the time was 50 min. The silk fibroin mixed solution was evenly divided into several disposable culture dishes, pre-frozen for 8 h (or treated with liquid nitrogen), and then wrapped with plastic wrap and pierced with holes, and freeze-dried to obtain silk fibroin / nano-scale ferric oxide composite aerogel; the aerogel was sealed in a plastic bag and stored in an electronic moisture-proof box.
[0087] Comparative Example 1:
[0088] (1) Preparation of cellulose
[0089] The holocellulose and a 5 wt % potassium hydroxide aqueous solution were mixed evenly according to a volume ratio of 1:10 g / mL of the absolute dry mass of the holocellulose and the potassium hydroxide aqueous solution, and the mixture was sealed and treated at 20° C. for 1 h. After the treatment, the mixture was transferred to a 500-mesh nylon mesh bag and repeatedly soaked and washed with deionized water until the material was neutral, and excess water was removed to obtain cellulose;
[0090] (2) Preparation of cellulose aerogel
[0091] The cellulose obtained in step (1) is added to deionized water, and then calcium thiocyanate tetrahydrate is added and mixed evenly, wherein the mass ratio of calcium thiocyanate tetrahydrate to cellulose is 12.5:1, and the mixture is heated and stirred at 90° C. until the system becomes uniform and transparent to obtain a uniform solution, wherein the concentration of the cellulose solution in the uniform solution is 0.5 wt %, and the uniform solution is added dropwise to an ethanol bath to form an aerogel, and after being soaked in deionized water, washed and purified, the aerogel is freeze-dried to obtain a cellulose aerogel;
[0092] (3) Preparation of modified cellulose aerogel
[0093] Deionized water, methacrylic acid and maleic acid were added to the cellulose aerogel obtained in step (2), wherein the mass ratio of cellulose aerogel to deionized water was 1:50 g / ml, the mass ratio of cellulose aerogel to methacrylic acid was 1:3, and the mass ratio of methacrylic acid to maleic acid was 1:5; nitrogen was passed through for 20 min (nitrogen flow rate was 0.1 nm 3 / h) and mixed evenly, and then added a mixed solution of hydrogen peroxide and ferrous chloride to initiate a graft copolymerization reaction; wherein the mass of cellulose aerogel and hydrogen peroxide is 1:0.015, and the molar ratio of hydrogen peroxide to ferrous chloride is 1:3, and the graft copolymerization reaction is carried out at a temperature of 45°C for 3h; after the reaction, the reactants are transferred to a Soxhlet extractor, extracted with water for 12h to remove the homopolymer, and the purified product is freeze-dried to prepare a modified cellulose aerogel for adsorbing heavy metals.
[0094] Test Example 1:
[0095] The BET specific surface area and porosity of the above-mentioned Examples 1 to 6 and Comparative Example 1 were measured, and the measurement results are specifically shown in Table 1;
[0096] Table 1 BET specific surface area and porosity of Examples 1 to 6 and Comparative Example 1
[0097]
[0098] As can be seen from Table 1, the silk-based composite aerogel material prepared by this scheme has a large BET specific surface area value, a good adsorption effect, less aggregation tendency between nano-scale particles, is not prone to agglomeration, and has good adsorption efficiency.
[0099] Test Example 2:
[0100] The heavy metal antimony adsorption test was carried out on the above-mentioned Examples 1 to 6 and Comparative Example 1. The specific operation was as follows: the silk fibroin-based composite aerogel material prepared above was placed in a 500 ml potassium antimony tartrate solution (initial concentration was 40 mg / L) -1 ) in a beaker, using a concentration of 1 mol / L -1The pH value of the solution was adjusted to 7 by sodium hydroxide and hydrochloric acid, and samples were taken at different adsorption times to determine the adsorption efficiency of the composite aerogel; and the adsorption capacity of the composite aerogel was measured by the adsorption kinetics determination method. The specific results are shown in Table 2.
[0101] Table 2 Adsorption rate and adsorption capacity of Examples 1 to 6 and Comparative Example 1
[0102]
[0103]
[0104] Depend on Figure 2 , Table 2 and Figure 3 It can be seen that under the same conditions, the adsorption rate and adsorption capacity of the silk-based composite aerogel material prepared in this scheme for metal antimony are significantly higher than the adsorption rate and adsorption capacity of the composite aerogel prepared in the comparative example for metal antimony.
[0105] Test Example 3:
[0106] The silk-based composite aerogel material prepared in Example 1 was put into textile printing and dyeing wastewater to carry out a heavy metal adsorption experiment. The heavy metal removal rate in the textile wastewater was tested at regular intervals. The specific results are shown in Table 3.
[0107] Table 3 Removal rate of heavy metals in textile printing and dyeing wastewater after administration
[0108] Pb(%) Cr(%) Hg(%) Cd(%) 10min 84 86 82 82 30min 85 89 84 86 60min 88 92 87 866 90min 90 91 87 86 120min 89 91 88 87
[0109] From Table 3 and Figure 4 It can be seen that the silk-based composite aerogel material prepared by this scheme can continuously adsorb heavy metals such as Pb, Cr, Hg and Cd in textile printing and dyeing wastewater, and the adsorption rate of these heavy metals can reach more than 82%.
Claims
1. A method for preparing a silk-based composite aerogel material for adsorbing heavy metals, characterized in that: The specific preparation method is as follows: (1) Using silk as raw material, degumming to obtain degummed silk, and then fully mixing it with a ternary system mixed solution, centrifuging, and dialyzing to obtain a silk fibroin solution; (2) mixing the nanoscale adsorbent and the silk fibroin solution at a certain mass fraction; (3) High-speed dispersion and freeze-drying of the solution blended in step (2) are performed to prepare a silk-based composite aerogel material.
2. The method for preparing a silk-based composite aerogel material for adsorbing heavy metals according to claim 1, characterized in that: In the degumming operation in step (1), a degumming agent is used, and the degumming agent is a 0.5wt% sodium carbonate solution, and the bath ratio of silk to sodium carbonate solution is 1:80-100.
3. The method for preparing a silk-based composite aerogel material for adsorbing heavy metals according to claim 1, characterized in that: The ternary system mixed solution in step (1) is a mixture of CaCl2, C2H5OH and H2O; the molar ratio of CaCl2, C2H5OH and H2O is 1:2:
8.
4. The method for preparing a silk-based composite aerogel material for adsorbing heavy metals according to claim 1, characterized in that: In the step (1), the mass ratio of the degummed silk to the ternary system mixed solution is 1:6-9; the reaction temperature is 50-70° C.; and the reaction time is 50-150 min.
5. The method for preparing a silk-based composite aerogel material for adsorbing heavy metals according to claim 1, characterized in that: The nanoscale adsorbent in step (2) is nanoscale ferric oxide, nanoscale ferroferric oxide or nanoscale aluminum oxide, and the particle size of the nanoscale adsorbent is less than 100 nm.
6. The method for preparing a silk-based composite aerogel material for adsorbing heavy metals according to claim 1, characterized in that: In the step (2), the mixing mass ratio of the silk fibroin solution to the nanoscale adsorbent is 1:1-10.
7. The method for preparing a silk-based composite aerogel material for adsorbing heavy metals according to claim 1, characterized in that: The high-speed dispersion speed in step (3) is 500 to 2000 r / min, and the dispersion time is 10 to 40 min.
8. The method for preparing a silk-based composite aerogel material for adsorbing heavy metals according to claim 1, characterized in that: The specific operation of freeze drying in step (3) is freezing at -70 to -40°C for 4 to 10 hours or vacuum drying after liquid nitrogen treatment.
9. The silk fibroin-based composite aerogel material obtained according to the method for preparing a silk fibroin-based composite aerogel material for adsorbing heavy metals according to any one of claims 1 to 8.
10. The use of the silk fibroin-based composite aerogel material in adsorbing heavy metals according to claim 9, characterized in that: The silk fibroin-based composite aerogel material is used for adsorbing heavy metals in textile printing and dyeing wastewater.
Citation Information
Cited By
Preparation method and application of 3D printing functional protein nano composite material
CN119771359A
Preparation method and application of tussah silk glue protein modified magnesium oxide adsorbent
CN121016693A
Silk fibroin modified magnetic hollow carbon microsphere composite material as well as preparation method and application thereof
CN122424793A
